Analysis of brain activity while performing cognitive actions to control a car - Nisar, H. (Springer Verlag, 2014)
In this paper we will present a real time brain computer interface system that operates a LEGO Mindstorms NXT car using the EEG signals produced by the electrical activity of brain. The brain signals are acquired using an EEG device and are translated into signals that can be understood by the NXT car. The NXT car moves according to the instructions provided. The experimental prototype uses an Emotiv EPOC headset that acquires data from 14 sensors to fully control the movement of a NXT Car. We have used the Cognitive states (intent of physical actions) and Expressive states (facial expressions) to control the NXT car. The system achieves more than 90 percent accuracy by using facial expressions however the accuracy of the system using cognitive actions is slightly above 80 percent. This technology is very useful for the disabled and elderly people as well as for those who work in dangerous environments. Â© Springer International Publishing Switzerland 2014.